Learning from previous disasters: Potential pitfalls of epidemiological psychosocial research in the COVID-19 environment. (July 2021) - Bell, Caroline; Beaglehole, Ben; Bell, Romana; Tanveer, Sandila; Sulaiman-Hill, Ruqayya; Boden, Joseph; Porter, Richard
It is critical to understand the psychosocial impacts of the COVID-19 pandemic on populations around the world. In this article, we highlight the key challenges associated with epidemiological psychosocial research in a disaster context and reflect on lessons learned from firsthand experience over the last decade in Christchurch, New Zealand, following the 2010/2011 Canterbury earthquakes and 2019 Mosque attacks. We make recommendations for study design to improve the quality of research evaluating the impacts of the COVID-19 pandemic, the inclusion of positive outcome measures and the need to evaluate a range of cultural contexts. We hope that highlighting these areas will improve research and result in a better understanding of the psychosocial impacts of the pandemic.